Interventions analysis of addressing exclusive breastfeeding (EBF) barriers to improve EBF coverage among industrial women employees in indonesia - Andari Wuri Astuti; Rosemary Morgan (Journal of Health Technology Assessment in Midwifery, 2018)
Low coverage of EBF is a global public health problem. Employment has been recognized as a factor that contributes to additional problems of EBF practice among women employees in Indonesia as they work more than 8 hours per day. In Indonesia, about 200,000 industrial companies which employed women in their production activities and they give only 3 months maternity leave. As a result, the coverage of EBF among industrial remains low. While policies already exist, the technical guidelines on the interventions are not well implemented due to unpractical approaches on these guidelines. This dissertation aims to analyse the interventions to address barriers of EBF in order to increase EBF coverage among industrial women employees in Indonesia. This is an in depth study using secondary data to review best practices to increase low coverage of EBF among industrial women employees. Propose of the study was to provide recommendations that could be implemented in Indonesian setting. The study show that there are three group level barriers i.e individual, group and social-culture contributed to low coverage of EBF. The analysis revealed that work place intervention such as lactation program and increasing employers’ awareness on breastfeeding are effective in implementation and feasible to be implemented in Indonesia. Another intervention is personal intervention i.e prenatal planning and preparation, job sharing and day care. It is recommended that those two interventions could be implanted simultaneously to address the barriers of EBF practice among industrial women employees in Indonesia.